Analysis and optimization on the performance of a heat pump water heater with solar-air dual series source. (December 2021) - Cai, Jingyong; Zhou, Haihua; Shi, Zhengrong; Chen, Haifei; Zhang, Tao
Abstract: Heat pump water heater can economize dramatic amounts of energy in domestic application. To make full use of hybrid heat source, a solar-air dual series source heat pump water heater (SA-HPWH) is proposed. The refrigerant can get vaporized in two types of evaporators to adjust to variable working conditions. Based on distributed modeling approach, the dynamic model of SA-HPWH system is established. The operational characteristics of the SA-HPWH system have been discussed under different working conditions. The results show that the SA-HPWH system is able to work effectively under low solar irradiation and ambient temperature. The average COP rises from 2.23 to 2.63 with T air rising from 10 °C to 20 °C. The rise in solar irradiation can lift the evaporating capacity of collector evaporator, while the value in air source evaporator decreases. The overall performance can be enhanced by rising G, and the average COP increases from 2.23 to 2.40 with G increasing from 100W/m 2 to 500W/m 2 . The rise of wind velocity can enhance heat transfer at air side, as well as COP, but the impact is not significant with the wind velocity exceeding 3m/s. In addition, the performance of the SA-SHPWH system can be further improved by utilizing PV/T collector.